2013
DOI: 10.1021/nn405392t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Gyroidal Mesoporous Carbons and Carbon Monoliths with Tunable Ultralarge Pore Size

Abstract: Ordered mesoporous carbons with high pore accessibility are of great interest as electrodes in energy conversion and storage applications due to their high electric and thermal conductivity, chemical inertness, and low density. The metal- and halogen-free synthesis of gyroidal bicontinuous mesoporous carbon materials with uniform and tunable pore sizes through bottom-up self-assembly of block copolymers thus poses an interesting challenge. Four double gyroidal mesoporous carbons with pore sizes of 12, 15, 20, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
158
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(163 citation statements)
references
References 43 publications
3
158
1
1
Order By: Relevance
“…DG‐structured templates are usually acquired from diblcok copolymer systems. For SG templates, we can selectively etch away one of the two chemically distinct DG channels in alternative DG systems . Figure a,b demonstrate the fabrication process of DG templates from AB systems and SG templates from ABC systems, respectively.…”
Section: Classification Of G Templatesmentioning
confidence: 99%
See 1 more Smart Citation
“…DG‐structured templates are usually acquired from diblcok copolymer systems. For SG templates, we can selectively etch away one of the two chemically distinct DG channels in alternative DG systems . Figure a,b demonstrate the fabrication process of DG templates from AB systems and SG templates from ABC systems, respectively.…”
Section: Classification Of G Templatesmentioning
confidence: 99%
“…Apart from solar cells, semiconductor metal oxides with DG morphology are also candidates for electrochromic and electrochemical pseudocapacitor devices, as we know that fast and efficient ion intercalation/extraction and electron transport for surface reaction are key factors determining the performances of electrochromic displays and electrochemical energy storage devices. GSFMs on a 10 nm length scale with their high specific surface area, interconnectivity, and structural integrity exactly fulfill these demands.…”
Section: Matter Transportmentioning
confidence: 99%
“…Following the BrunauerÀEmmettÀTeller (BET) method, the specific surface area has been estimated as 885 m 2 g À1 , which is comparable to that reported in the literature. 32 As shown in Figure 5b and c, the sample has been found to have pores with sizes in both the micro and meso ranges. The SF (SaitoÀFoley) and BJH (BarrettÀJoynerÀHalenda) methods have been employed to estimate the pore sizes in the micro (<2 nm) and meso ranges (2À 50 nm), respectively.…”
Section: Articlementioning
confidence: 86%
“…31 Recently Wiesner et al also reported the fabrication of porous carbon material using block copolymers with gyroid structure. 32 In this study, we explore the fabrication and characterization of such novel carbon materials by employing polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) block copolymers and the amphiphilic molecule 3-pentadecylphenol (PDP), which together form a gyroid morphology as a sacrificial template. We apply the obtained nanoporous carbon as a material to design cathodes for lithium sulfur batteries, which have a very high theoretic specific energy of 2600 Wh/kg due to the extraordinary theoretical specific capacity of 1675 mAh/g of sulfur.…”
mentioning
confidence: 99%
“…Note that the alignment of the different structures was performed using all the atoms of GNC structures. Further, the RMSF gives information about the local rigidity/flexibility of an atom of a given system during a MD run: (2) where N time is the production time of the MD simulation and ⟨r i ⟩ is the average position of atom i. Note the difference between the information included in RMSD and RMSF: RMSF implements averages over time (N time ), yielding a different value for each atom i while RMSD uses ensemble averaging over all the particles (N atom ), at a given time value t.…”
Section: ■ Introductionmentioning
confidence: 99%